The path to personalized medicine in asthma. (1st September 2016) - Bagnasco, Diego; Ferrando, Matteo; Bernardi, Stefano; Passalacqua, Giovanni; Canonica, Giorgio Walter
ABSTRACT: Introduction : Asthma is a common respiratory disorder, since about 10% of the population suffer from this disease, and up to 10% have a severe form. Recent findings have allowed a greater and deeper understanding of the pathophysiological mechanisms, distinguishing two groups of patients according to the prevalent cellular population that drives the inflammatory process, and consequentially, to intervene on different cellular targets. Areas covered : Currently, several biological drugs directly interfering with these pathophysiological mechanisms (namely IgE, IL-4, IL-5, IL-13, and IL-17) are under investigation. Expert commentary : With the elucidation of mechanisms, new-targeted drugs have been developed. Asthma therapy is changing from a 'one size fits all' therapy to a 'precision medicine' model, where we may prescribe the most appropriate treatment for each patient. Moreover, in the near future, the possibility to act a 'sequential bio-combination therapy' can be envisaged, using different biological drugs in the same patient to act on different pathophysiological mechanisms.